2020
DOI: 10.3390/pathogens9110947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Concentrated and Concentrated Vaporized Hydrogen Peroxide on Scrapie Prions

Abstract: To date, there have been no studies on the sterilization of prions by non-concentrated and concentrated vaporized hydrogen peroxide (VHP) applied by the same instrument. Here, the effect of the two types of VHP applied using an ES-700 sterilizer on prions was investigated. Brain homogenate from scrapie (Chandler) prion-infected mice was spotted on a cover glass and subjected to ES-700 treatment in soft (non-concentrated VHP from 59% hydrogen peroxide) or standard (concentrated VHP from 80% hydrogen peroxide) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…In the present study, we compared ozone gas, hydrogen peroxide gas, and ozone-mixed hydrogen peroxide gas for their activities to inactivate prion infectivity, by exposing RML prions contaminated on stainless steel wires to each gas and then implanting the treated stainless steel wires into the brains of mice. Consistent with the results previously reported by others showing that ozone and hydrogen peroxide gas could inactivate prion infectivity [19][20][21]24,25 , we found that mice implanted with ozone gas-or hydrogen peroxide gas-exposed, RML prion-contaminated wires developed the disease signi cantly longer than those implanted with gas-unexposed, RML prion-contaminated wires. However, incubation times of mice implanted with ozone-mixed hydrogen peroxide gas-exposed, RML prion-contaminated wires were much longer than those of mice implanted with ozone gas alone-or hydrogen peroxide gas alone-exposed, RML prion-contaminated wires.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we compared ozone gas, hydrogen peroxide gas, and ozone-mixed hydrogen peroxide gas for their activities to inactivate prion infectivity, by exposing RML prions contaminated on stainless steel wires to each gas and then implanting the treated stainless steel wires into the brains of mice. Consistent with the results previously reported by others showing that ozone and hydrogen peroxide gas could inactivate prion infectivity [19][20][21]24,25 , we found that mice implanted with ozone gas-or hydrogen peroxide gas-exposed, RML prion-contaminated wires developed the disease signi cantly longer than those implanted with gas-unexposed, RML prion-contaminated wires. However, incubation times of mice implanted with ozone-mixed hydrogen peroxide gas-exposed, RML prion-contaminated wires were much longer than those of mice implanted with ozone gas alone-or hydrogen peroxide gas alone-exposed, RML prion-contaminated wires.…”
Section: Discussionsupporting
confidence: 92%
“…However, medical instruments or devices are so complicated and delicate that they may be susceptible to the damages that the chemicals or autoclaving may cause. Effective reduction of prion infectivity has been also reported with gas sterilizations, including hydrogen peroxide gas sterilization 19,20 . Mixing of ozone solution in prion-infected brain homogenates was also shown to reduce prion infectivity in the homogenates 21 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some guidelines state that peracetic acid is ineffective or sub-optional for decontamination and reducing the infectivity of prions [ 18 , 35 ]. By contrast, a few studies have shown that VHP inactivates prions [ 15 , 27 , 28 ]. For example, it is well established that hydrogen peroxide gas plasma can inactivate prions [ 36 ]; with this technology, hydrogen peroxide gas is used for the sterilization process, while the plasma is generated at a later stage of the cycle and is not thought to play a significant, if any, role in sterilization [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of other potential methods for inactivating prions on heat-sensitive medical devices, including VHP [ 28 ], hydrogen peroxide gas plasma [ 15 ], copper (0.5 mmol/L) plus hydrogen peroxide (100 mmol/L) (1 h, room temperature) [ 15 ], and electrically charged disinfectants [ 39 ]. Future work should assess the effectiveness of these approaches relative to VHPPA treatment, in addition to combinations of treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation